Aktualisasi Teori Hierarki Kebutuhan Abraham H. Maslow bagi Peningkatan Kinerja Individu dalam Organisasi - Lianto, Lianto (MABIS, 2011)
In this article, the theory of Abraham H. Maslowâs Hierarchy of Needs would be the starting point and the foundation for the idea of finding motivation to increase the performance of individuals within the organization. Today, there are various criticisms about the validity of Maslowâs theory. However, as a basic concept for the introduction of individual personality and various structural factors that encourage people to do something, this theory can still resonates loudly. The term "actualization" is meant how Maslows theory in social psychology can be adopted into individual motivation in the management disciplines and how the theory, which was introduced in the 1950s, can be re-actualized